2018
DOI: 10.1016/j.kjms.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Dental deafferentation and brain damage: A review and a hypothesis

Abstract: In the last few decades, neurobiological and human brain imaging research have greatly advanced our understanding of brain mechanisms that support perception and memory, as well as their function in daily activities. Knowledge of the neurobiological mechanisms behind the deafferentation of stomatognathic systems has also expanded greatly in recent decades. In particular, current studies reveal that the peripheral deafferentations of stomatognathic systems may be projected globally into the central nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 73 publications
0
3
0
5
Order By: Relevance
“…The activation of different areas of the cerebral cortexresulting from chewing had already been previously proposed in studies where the mastication of chewing gum demonstrated an increase in regional blood flow of the brain in areas such as the primary sensorimotor area, complementary motor areas, insula, cerebellum and corpus striatum (Momose et al, 1997). Given that a deterioration in masticatory function is dependent on the presence of teeth, current studies suggest that the process of peripheral deafferentation in the stomatognathic system could project globally in the central nervous system and become a critical factor that could trigger and/or aggravate neurodegenerative diseases (Jou, 2018). A recent qualitative systematic review indicates that masticatory function can act as a protective factor in subjects with cognitive decline and neurodegenerative diseases by increasing cerebral blood flow.…”
Section: Chewing and Cognitive Functionmentioning
confidence: 78%
“…The activation of different areas of the cerebral cortexresulting from chewing had already been previously proposed in studies where the mastication of chewing gum demonstrated an increase in regional blood flow of the brain in areas such as the primary sensorimotor area, complementary motor areas, insula, cerebellum and corpus striatum (Momose et al, 1997). Given that a deterioration in masticatory function is dependent on the presence of teeth, current studies suggest that the process of peripheral deafferentation in the stomatognathic system could project globally in the central nervous system and become a critical factor that could trigger and/or aggravate neurodegenerative diseases (Jou, 2018). A recent qualitative systematic review indicates that masticatory function can act as a protective factor in subjects with cognitive decline and neurodegenerative diseases by increasing cerebral blood flow.…”
Section: Chewing and Cognitive Functionmentioning
confidence: 78%
“…Длительное время считалось, что стоматологические проблемы возникают из-за трудностей при осуществлении ухода за полостью рта в случаях ухудшения когнитивных функций, памяти и физических способностей у пациентов с деменцией. Однако в недавних исследованиях высказывается предположение, что потеря зубов и окклюзионная дисфункция также могут влиять на когнитивные функции и вызывать развитие деменции [41].…”
Section: влияние физической активности на когнитивный статусunclassified
“…Нейровизуализационные исследования с использованием функциональной магнитнорезонансной томографии (фМРТ) показали, что во время жевания возникает активация нескольких областей головного мозга (первичной соматосенсорной коры, первичной моторной коры, дополнительной моторной коры, премоторной коры, префронтальной коры, островка, задней теменной коры, таламуса, стриатума и мозжечка). Потеря зубов оказывает влияние на координацию зубного ряда той же дуги, а также зубного ряда на противоположной дуге во время жевания и может вызывать сенсорную и моторную реорганизацию коры головного мозга [41,42].…”
Section: влияние физической активности на когнитивный статусunclassified
“…When one of these 'musicians' change their function or are removed, it results in structural and functional deafferentations of the adjacent and opposing teeth. This causes a mistune in the 'natural melody' and leads to sustained and even permanent reorganizations of sensory and motor cortices [6]. However, this ability for reorganization dwindles as age progresses, thereby leaving edentulous geriatric patients more susceptible to cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%